Lexicons in Ajisaka Dance - Suryandewi Komang (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Ajisaka dance is a traditional Balinese dance that has lexicons and their cultural meaning. The ones who practice and perform the dance do not know about the lexicons of the dance. It can cause language death because the native speaker does not maintain their language. This study aimed to find out the lexicons and their cultural meaning related to Ajisaka dance movements. The setting of this study was conducted in Buleleng regency. It was designed in the form of a qualitative method using an ecolinguistic approach. The data were obtained through observation and interview techniques. The results of the study show that the lexicons are classified into eye movements (two lexicons), neck movements (two lexicons), body movements (four lexicons), hand movements (eight lexicons), finger movements (four lexicons), and leg movements (eight lexicons) and the cultural meaning of the lexicons of movements refers to the firmness, obedience to responsibility, authority, majesty, intelligence and agility, the subtlety of mind and soul, and the strong principles of the king and his soldiers. The results of this study can be used as teaching material for the dance teacher to teach lexicons and their cultural meaning to their students and introduce it to foreigners who want to learn this dance. Specifically, this study can help maintain a local language and lead to avoiding language death.Â Keywords: ecolinguistic; lexicons; cultural meaning; Balinese dance; Ajisaka dance